The Efficacy of Artificial Intelligence (AI) Adoption in Enhancing Social Media Marketing Creativity for Micro, Small, and Medium Enterprises (MSMEs) in North Sumatra: A Comprehensive Investigation - Achmad Puariesthaufani N; Satria Tirtayasa (CV. Akira Java Bulu, 2026)
This research investigates the efficacy of Artificial Intelligence (AI) adoption in enhancing social media marketing creativity among Micro, Small, and Medium Enterprises (MSMEs) in North Sumatra. It examines how AI tools influence ideation, content generation, and strategic execution of marketing campaigns. Amidst digital transformation, social media platforms are crucial for MSMEs, and AI offers transformative potential for optimizing marketing efforts and fostering creativity. Despite AI's growing recognition, empirical evidence on its impact on MSME marketing creativity, especially in developing economies, remains limited, highlighting a gap in understanding its nuanced influence beyond mere automation. Employing a qualitative descriptive approach, this study utilizes semi-structured interviews to explore the lived experiences of MSME representatives, analyzing themes related to AI adoption, marketing creativity, and productivity. Preliminary quantitative data from 350 respondents indicates varying levels of AI usage across regions, with social media marketing widely adopted but direct AI application for product design less prevalent. Findings suggest that AI integration significantly enhances ideation, content originality, and strategic campaign alignment, positioning AI as a catalyst for creativity and marketing productivity for resource-limited MSMEs. This study contributes empirically by quantifying AI's impact, demonstrating its role as a strategic partner in unlocking creative expression and driving superior marketing outcomes for MSMEs in North Sumatra.